Group living facilitates the evolution of duets in barbets. (26th August 2020) - Soma, Masayo; Brumm, Henrik
Abstract : The duets of birds have intrigued biologists for a long time, yet much remains unknown about the evolution of these striking collective displays. This is partly because previous studies on duet evolution have been biased to songbirds and neglected other bird groups. In songbirds, the absence of migration has been found to predict the occurrence of duetting, indirectlysupporting the idea that duet communication is linked with pair bonding. Here, we used phylogenetic comparative analyses in a sedentary clade of non-songbirds, the barbets (Capitonidae), to reveal new correlates of duet evolution. We found (i) that duets evolved several times independently in different barbet lineages and (ii) that duetting evolved in association with group living (i.e. the presence of helpers or non-breeding adults during the breeding period), but not with sexual monochromatism or habitat type. Our findings are consistent with a duet function in mate guarding and dominance against subordinate group members as well as joint territory defence. Altogether, the results highlight the importance of the social environment for the evolution of collective signalling.